The α-Gliadins in Bread Wheat: Effect of Nitrogen Treatment on the Expression of the Major Celiac Disease Immunogenic Complex in Two RNAi Low-Gliadin Lines - Sánchez-León, Susana; Giménez, María José; Barro, Francisco (Frontiers in Plant Science, 2021)
Celiac Disease (CD) is an autoimmune disorder that affects approximately 1% of the worldwide population. The α-gliadins of wheat contain the 33-mer peptide, the most active peptide in CD both in adults and pediatric patients. In this study, we have characterized the variants and expression profile of an α-gliadins amplicon, harboring the 33-mer peptide, in two low-gliadin RNAi wheat lines, under two different Nitrogen (N) treatments. We estimated that the amplicon expands 45 different α-gliadin variants with high variability due to length, randomly distributed SNPs, and the presence of encoded CD epitopes. Expression of this amplicon is reduced in both RNAi lines in comparison to the wild type. High N treatment significantly increases transcripts of the amplicon in the wild type, but not in the transgenic lines. Classification of α-gliadin variants, considering the number of epitopes, revealed that amplicon variants containing the full complement of 33-mer peptide were affected by N treatment, increasing their expression when N was increased. Line D793 provided higher and more stable silencing through different N fertilization regimes, expressing fewer CD epitopes than D783. Results of this study are important for better understanding of RNAi α-gliadin silencing in response to N treatments, and for undertaking new strategies by RNAi or CRISPR/Cas towards obtaining new varieties suitable for people suffering gluten intolerances